ANALISIS KARAKTERISTIK MUTU NATA DE LERI DENGAN VARIASI KONSENTRASI GULA PASIR SEBAGAI SUMBER KARBON - Andi Maryam (Cross-border, 2020)
Nata de leri is nata that is processed using rice washing water which has the potential to become a fiber-rich snack. The purpose of this study was to determine the yield, thickness, and fiber content of nata de leri with variations in the concentration of granulated sugar as a carbon source (ie 5% and 10% granulated sugar). The results showed that Nata de leri with 5% sugar concentration produced 66.14% yield, 0.62 cm thickness, and 14.21% fiber content, while the 5% granulated sugar treatment had 45.31% yield, thickness 0, 67 cm, and 12.20% fiber content.